Exploring the mechanism of the Pd-catalyzed spirocyclization reaction: a combined DFT and experimental study - Franzoni, Ivan (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
The mechanism of the palladium-catalyzed spirocyclization of acrylamides has been investigated by density functional theory and experimental studies. The results support a mechanistic pathway that proceeds via oxidative addition, intramolecular carbopalladation, C–H bond activation, and migratory insertion sequence. The M06L/def2-TZVPP//BP86/6-31G(d,p)/LANL2DZ level of theory used and the inclusion of solvent effects provide results in good agreement with the experimental data. The C–H bond activation step proceeds via a concerted outer-sphere metallation deprotonation mechanism that explains the absence of a measurable kinetic isotopic effect. The subsequent intermolecular migratory insertion of arynes is significantly faster than the insertion of internal alkynes. Furthermore, the regioselectivities calculated in the case of unsymmetrical reactants are remarkably close to the experimental values. Evaluation of the potential energy surfaces for specific substrates provides an explanation for the lack of product formation observed experimentally. Finally, the computational and experimental analyses of potential side reactions are also presented and support the initially proposed mechanism.